2015
DOI: 10.1103/physrevb.92.144405
|View full text |Cite
|
Sign up to set email alerts
|

All-electrical manipulation of magnetization dynamics in a ferromagnet by antiferromagnets with anisotropic spin Hall effects

Abstract: We investigate spin-orbit torques of metallic CuAu-I-type antiferromagnets using spin-torque ferromagnetic resonance tuned by a dc-bias current. The observed spin torques predominantly arise from diffusive transport of spin current generated by the spin Hall effect. We find a growth-orientation dependence of the spin torques by studying epitaxial samples, which may be correlated to the anisotropy of the spin Hall effect. The observed anisotropy is consistent with first-principles calculations on the intrinsic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 63 publications
(75 reference statements)
6
78
4
Order By: Relevance
“…For the materials considered here this has been done elsewhere. 38 In this work the phenomenological torque model combined with an angular dependent study strengthens previous results 38 and points to new directions of future work. Because the two torques in Eq.…”
Section: The Classic "Two-torque" Modelsupporting
confidence: 64%
See 3 more Smart Citations
“…For the materials considered here this has been done elsewhere. 38 In this work the phenomenological torque model combined with an angular dependent study strengthens previous results 38 and points to new directions of future work. Because the two torques in Eq.…”
Section: The Classic "Two-torque" Modelsupporting
confidence: 64%
“…We recently confirmed large spin current generation from such metallic AFs, in particular PtMn, through ST-FMR experiments. 38 Furthermore, we showed that the strength of the STT in ST-FMR experiments could be controlled by utilizing different crystal structures of the same AF materials. 38 Here, we will build on this work by presenting a systematic study of the ST-FMR lineshapes as a function of the in-plane angular direction.…”
Section: Antiferromagnets: Materials Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…The AFM-induced torques and their correlation with the exchange coupling at the FM/AFM interface could lead to novel designs of spintronic devices. After completing our work we learned about a related study on electrical manipulation of magnetization dynamics in a ferromagnet by antiferromagnets [45].…”
Section: Discussionmentioning
confidence: 99%